"In the Face, a Right Is There": Arendt, Levinas and the Phenomenology of the Rights of Man. Issue 49 (2nd October 2018) - Bell, Nathan
ABSTRACT: This paper examines the differences between the thought of Hannah Arendt and Emmanuel Levinas concerning the "Rights of Man", in relation to stateless persons. In The Origins of Totalitarianism, Arendt evinces a profound scepticism towards this ideal, which for her was powerless without being tethered to citizenship. But Arendt's own idea of the "Right to have Rights" is critiqued here as being inadequate to the ethical demand placed upon states by refugees, in failing to articulate just what states might be responsible for . I argue that the ethical philosophy of Levinas meets this lacuna in Arendt's thought, via his concept of the Face as the locus of human dignity and to which states can be recalled to responsibility. Levinas wrote several papers on what he called "the phenomenology of the Rights of Man", and in his phrase, which provides a summation of precisely what is lacking in Arendt's arguments: "In the face – a right is there".